Surveys for natural enemies of the tomato red spider mite Tetranychus evansi (Acari: Tetranychidae) in northeastern and southeastern Brazil - Fiaboe, K.K.M.; Gondim, M.G.C.; Moraes, G.D.; Ogol, C.K. de; Knapp, M. (Magnolia Press, 2007)
Surveys for predators of the tomato red spider mite Tetranychus evansi Baker & Pritchard on solanaceous plants were carried out in north-eastern and south-eastern Brazil to determine prospective species for the control of the pest in Africa. Surveys were carried out in areas identified as climatically similar to regions in Africa where T. evansi has been reported as a pest and where prospective natural enemies may be introduced. A total of 56,445 mites and insects were found in 330 samples collected from 20 different species of solanaceous plants. Tetranychus evansi was found in only three samples, on Solanum americanum Mill. and Lycopersicon esculentum Mill.. A total of 5,023 specimens of predatory mites, of at least 44 species, and 494 specimens of acarophagous insects, of at least three species were collected. The predominant predatory mites were (in decreasing order): Phytoseius guianensis DeLeon, Pronematus ubiquitus (McGregor), Asca sp., Paraphytoseius orientalis (Narayanan, Kaur & Ghai), Phytoseius woodburyii DeLeon, Amblyseius compositus Denmark & Muma, Homeopronematus anconai (Baker), Neoparaphytoseius sooretamus (El-Banhawy), Cunaxoides sp., Typhlodromus paraevectus Moraes & McMurtry, Typhlodromalus peregrinus (Muma) and Phytoseius cismontanus DeLeon. However, no predatory mites were found in association with T. evansi. Among the insects, although not the most abundant, Stethorus tridens Gordon seemed to be most promising, as it was found associated with T. evansi in all samples in which the latter was found. Feltiella sp. was the most abundant acarophagous insect found, but it was never found associated with the pest.